Solution Let f(n) be the desired result. There is a \binom{n}{k} / 2^n chance that k of them will show heads, and the process is repeated with n-k coins now. The rest of the game is expected to take f(n-k) throws. If k=0 then we still have the same situation as before. If k=n, we have 0 throws left. In all of these situations, we do have to spend 1 turn doing the throw. So the recurrence relation is:
f(n) = 1 + \sum_{k=1}^{n-1} \frac{\binom{n}{k}}{2^n} f(k) + \frac{1}{2^n}f(n) f(n) = \frac{2^n + \sum_{k=1}^{n-1} \binom{n}{k} f(k)}{2^n-1}
Given a large n, computing this would take O(n^2) time as we have to calculate and store the previous f(k) values, and each take O(k) time. We can manipulate this expression further to come with a summation formula for f(n) that would allow it to be computed in linear time.
First we claim and prove the following lemma. For 1 \leq m < n
\sum_{k=m}^{n} \binom{n}{k}\binom{k}{m} = \binom{n}{m}2^{n-m}
Proof: given n white balls, we wish to pick m of them and paint them black, and the rest may stay white or be painted gray. The RHS side is obvious, there are \binom{n}{m} ways to choose black balls, and the rest may be painted white or gray.
To show the LHS, first we pick a number k \in [m,n]. We choose k balls and paint them gray. Out of these k, we further choose m to be painted black.
Alternatively we can prove the lemma by dividing both sides by \binom{n}{m}: \sum_{k=m}^{n} \frac{n!}{k!(n-k)!} \frac{k!}{m!(k-m)!} \frac{m!(n-m)!}{n!} = 2^{n-m} \sum_{k=m}^{n} \frac{(n-m)!}{(n-k)!(k-m)!} = 2^{n-m} \sum_{i=0}^{n-m} \frac{(n-m)!}{(n-m-i)!i!} = 2^{n-m}
which is a well-known identity
Given the lemma, now we claim the following statement: let a_n = \frac{2^n}{2^n-1} then: f(n) = \binom{n}{1}a_1 - \binom{n}{2}a_2 + \binom{n}{3}a_3 + \dots + (-1)^{n+1} \binom{n}{n}a_n We will show that this formula matches our recurrence relation above by strong induction. Suppose they hold for 1,2,\dots,n-1, then we first evaluate the following expression: \sum_{k=1}^{n-1} \binom{n}{k}f(k) = \binom{n}{1}f(1) + \binom{n}{2}f(2) + \dots + \binom{n}{n-1}f(n) = \sum_{k=1}^{n-1} \binom{n}{k} \sum_{m=1}^{k} (-1)^{m+1} \binom{k}{m}a_m we rearrange and collect each a_m terms: = \sum_{m=1}^{n-1} (-1)^{m+1}a_m \sum_{k=m}^{n-1} \binom{n}{k} \binom{k}{m} Apply the lemma: = \sum_{m=1}^{n-1} (-1)^{m+1}a_m \left(\binom{n}{m}2^{n-m} - \binom{n}{m} \right) = \sum_{m=1}^{n-1} (-1)^{m+1} \binom{n}{m} a_m \left(2^{n-m} - 1 \right) We can plug this expression to our recurrence formula and compare against our claim (induction hypothesis). After multiplying both sides by 2^n-1, we are left to show that: (2^n-1) a_n + \sum_{m=1}^{n-1} (-1)^{m+1} \binom{n}{m} a_m \left(2^{n-m} - 1 \right) = (2^n-1) \left( \sum_{m=1}^{n-1} (-1)^{m+1} \binom{n}{m}a_m + (-1)^{n+1}a_n \right) Collect a_n terms to the LHS, and the rest of the terms to RHS: (2^n-1)(1 + (-1)^n)a_n = \sum_{m=1}^{n-1}a_m(-1)^{m+1} c_m where c_m = (2^n-1)\binom{n}{m} - \binom{n}{m}(2^{n-m}-1) = \binom{n}{m}(2^n - 2^{n-m}) = \binom{n}{m}2^{n-m}(2^m-1) = \binom{n}{m}2^{n-m} \frac{2^m}{a_m} so what we need to show becomes: (2^n-1)(1 + (-1)^n)a_n = \sum_{m=1}^{n-1}a_m(-1)^{m+1} \binom{n}{m}2^{n-m} \frac{2^m}{a_m} 2^n(1 + (-1)^n) = \sum_{m=1}^{n-1}(-1)^{m+1} \binom{n}{m}2^{n} 1 + (-1)^n = \sum_{m=1}^{n-1}(-1)^{m+1} \binom{n}{m} 1 + \sum_{m=1}^{n-1}(-1)^{m} \binom{n}{m} + (-1)^n = 0 (1 -1)^n = 0
No comments:
Post a Comment